2012
DOI: 10.1515/cclm.2011.881
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix-associated (GAGs, CTGF), angiogenic (VEGF) and inflammatory factors (MCP-1, CD40, IFN-γ) in type 1 diabetes mellitus nephropathy

Abstract: Conclusively, increased GAGs and CTGF excretion are evident in T1DM normoalbuminuric juveniles, possibly reflecting early renal injury signs, before the initiation of albuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…And the loganin related gene, i.e. CTGF was associated with diabetes and diabetic nephropathy 7478 , which was also consistent with our results.
Figure 5The pharmacology network generated for LDW. The innermost circle represented the compounds collected from LDW, the circle in the middle represented the related genes of compounds from LDW, the outermost layer represented the diseases that were related to the genes.
…”
Section: Resultssupporting
confidence: 87%
“…And the loganin related gene, i.e. CTGF was associated with diabetes and diabetic nephropathy 7478 , which was also consistent with our results.
Figure 5The pharmacology network generated for LDW. The innermost circle represented the compounds collected from LDW, the circle in the middle represented the related genes of compounds from LDW, the outermost layer represented the diseases that were related to the genes.
…”
Section: Resultssupporting
confidence: 87%
“…CTGF (connective tissue growth factor), a member of CCN family of extracellular matrix-associated heparin-binding proteins, has an essential role in cell adhesion, migration, proliferation and angiogenesis 52, 53 . Aberrant CTGF expression is associated with diabetic nephropathy 54 , retinopathy 55 and cardiovascular diseases 56 . GDF1 is a key regulator in the establishment and maintenance of Left-Right (L-R) signals governing asymmetric organogenesis, including the heart and the great vessels 57 .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have described an increased urinary GAGs excretion compared to controls, even in normoalbuminuric patients [9496, 99, 100, 102–111]. But one study found similar urinary GAGs excretions in normoalbuminuric diabetic patients and healthy controls [102].…”
Section: Glycosaminoglycansmentioning
confidence: 99%